Pengaruh Penerapan Model Pembelajaran Team Assisted Individually (TAI) Terhadap Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa SMA - Dewi Nurrizki; Reviandari Widyatiningtyas; Elly Retnaningrum (EDUCARE, 2016)
This study aims to obtain empirical evidence about the effect of the TAI learning model on improving the mathematical problem solving abilities of high school students. This study used a quasi-experimental method with a non-equivalent control group research design. The instrument used for this study was a test of students' mathematical problem solving abilities to obtain quantitative data and observation sheets for the implementation of learning in the experimental class. Quantitative data analysis in this study used the normality test, variance homogeneity test, and average difference test. While the results of the observation sheet to describe the implementation of learning in class. The results of the study were obtained as follows. (1) There is an increase in mathematical problem solving abilities of high school students using the TAI learning model. (2) Improvement of mathematical problem solving abilities of high school students who use the TAI learning model is better than high school students who use conventional learning models.